Linking Assessment to Instruction: Using Dynamic Indicators of Basic E arly Literacy Skills in an Outcomes-Driven Model - Kaminski, Ruth; Cummings, Kelli (Dynamic Measurement Group, 2008)
As educators increasingly are held responsible for student achievement , school personnel struggle to find ways to effectively document stude nt responsiveness to interventions and track progress toward important outcomes. While many educators focus on high-stakes tests as a means of documenting student achievement of important outcomes, other assess ment approaches may be better suited to assessing student progress. As sessment that can be used to adapt teaching to meet student needs is c alled formative assessment. Because the primary purpose of formative a ssessment is to support student learning, it may arguably be considere d the most important assessment practice in which educators engage. Th is paper will focus on linking assessment to instruction to improve st udent outcomes through the use of Dynamic Indicators of Basic Early Li teracy Skills (DIBELS) within an Outcomes-Driven Model.